ANALISIS DAMPAK TATA KELOLA PERUSAHAAN, STRUKTUR KEPEMILIKAN DAN CASH HOLDINGS TERHADAP NILAI PERUSAHAAN DI BEI 2014-2018 - Budi Chandra; Cindy Feliana (Jurnal Ilmiah Akuntansi Indonesia, 2020)
Implementation of corporate governance is expected to provide prosperity and welfare for shareholders. This study intended to analyze the impact of board size and audit quality proxies from corporate governance on firm value. This study also uses managerial ownership which is proxies from ownership structure and also cash holdings to analyze deeper its impact on firm value. There were also three control variables: leverage, firm size and firm age.Companies listed in the Indonesia Stock Exchange in 2014 to 2018 were objects that supporting this research. Data collection utilizes purposive sampling method and selected according to the criteria of 448 companies. Companies that met the criteria were further tested using the panel regression method to analyze the existing influence between the independent variable and dependent variable.The findings obtained in this study indicate that there is no significant relationship between board size and audit quality on firm value. Meanwhile, managerial ownership and cash holdings prove that there is a significant positive correlation to firm value. Then for the control variable, leverage does not affect the value of the company, but the size and age of the company both have a significant positive effect on firm value.